Impact of Systematic Tailored Assessment for Responding to Suicidality (STARS) Protocol Training on Mental Health Professionals' Attitudes, Perceived Capabilities, Knowledge, and Reluctance to Intervene - Hawgood, Jacinta; Ownsworth, Tamara; Kõlves, Kairi; Spence, Susan H.; Arensman, Ella; De Leo, Diego (Frontiers in Psychiatry, 2022)
Background and aims: Systematic Tailored Assessment for Responding to Suicidality (STARS) protocol and associated training were developed with the key objectives of supporting clinicians to conduct a suicide enquiry, obtain a comprehensive account of psycho-social factors contributing to suicidality, and collaboratively develop a safety plan with clients. STARS training aims to address knowledge, attitudes and capabilities that influence intervention behaviour/skills. This study aimed to examine associations between clinician characteristics and pre-training competencies in suicide risk assessment (SRA), as well as the impact of STARS training workshop on clinician competencies; and to determine the predictors of SRA training outcomes. Method: Australian mental health professionals working with suicidal persons who undertook the STARS two-day face-to-face workshop between 2018 and 2020 completed an online survey at pre- and post-training. Of the 222 participants who completed the pre-training questionnaire, 144 (64.9%) also completed the post-training questionnaire. Participants were mostly female (75.7%), had completed a university degree (86.4%), had less than 10 years of experience in suicide prevention (71.7%), and were allied and mental health professionals (78.1%). We used linear mixed-effects regression for statistical analyses. Results: STARS participants who reported higher perceived capability at baseline had significantly greater formal and informal training, more years of experience in suicide prevention, and were more likely to have experienced client suicide and/or suicide attempt and to report fewer SRA related fears. We found overall significant positive impacts of STARS training on clinician competencies (attitudes, perceived capability, declarative knowledge) from pre- to post-training. The most distinct changes following STARS training were for perceived capability and declarative knowledge. Participants who had more positive attitudes after training were significantly more likely to have had less prior supervision/mentoring. Reluctance to intervene was not found to significantly change after training. Conclusions: We found evidence that attitudes, perceived capability and declarative knowledge changed positively from pre- to post-STARS training among mental health professionals. Underpinned by the minimum standardised SRA competencies, STARS training may be critical for informing evidence-based knowledge and skills in SRA and safety planning.